Hubungan Pola Makan Dengan Gastritis Pada Remaja Di SMK Kesehatan Napsi’ah Stabat Kabupaten Langkat - Siska Wati Amri (Universitas Malahayati Lampung, 2020)
ABSTRACT: THE RELATIONSHIP OF EATING PATTERNS WITH GASTRITIS IN ADOLESCENTS IN NAPSI'S VOCATIONAL SCHOOL OF HEALTH, STEP STATEMENTS, LANGKAT REGENCYBackground:Teenagers are often stuck with unhealthy eating patterns, even to the point that eating disorders can cause gastritis. Gastritis is an inflammation of the stomach mucosa that is acute and chronic. Diet is a variety of information that provides an overview of the type and amount of food eaten every day by one person and is characteristic for a particular group of people.Purpose : The purpose of this study is for the relationship between eating patterns and gastritis in adolescents at Stabat Napsi'ah Health Vocational School in 2018 Method:This type of research used in this study is an observational analytic study with a cross sectional study approach. Total population of 32 people, the sample used in this study was a total sampling of 32 people. Result:Data analysis using chi square test with a degree of confidence p 0.05. Based on the results of the chi square test the relationship of eating patterns with gastritis in adolescents at Stabat Napsi'ah Health Vocational School in 2018 with a degree of significance (α) = 0.05 and df = 1, the calculation results obtained are Sig (2-tailed) 0.001 (α) = 0.05, then Ho is rejected and Ha is accepted.Conclusion: The conclusion is that there is a relationship between diet and gastritis in adolescents at Stabat Napsi'ah Health Vocational School in 2018. It is recommended that you maintain a good diet, especially at the frequency of eating with regular meals, full meals 3 times a day or by food. Keywords : Dietary Habit, GastritisINTISARI: HUBUNGAN POLA MAKAN DENGAN GASTRITIS PADA REMAJA DI SMK KESEHATAN NAPSI’AH STABAT KABUPATEN LANGKAT Latar Belakang: Remaja sering terjebak dengan pola makan yang tidak sehat, bahkan sampai gangguan pola makan yaitu dapat menyebabkan gastritis. Gastritis adalah suatu peradangan mukosa lambung yang bersifat akut dan kronik. Pola makan adalah berbagai informasi yang memberikan gambaran mengenai macam dan jumlah bahan makanan yang dimakan setiap hari oleh satu orang dan merupakan ciri khas untuk suatu kelompok masyarakat tertentu.Tujuan : Tujuan penelitian ini untuk hubungan pola makan dengan gastritis pada remaja di SMK Kesehatan Napsi’ah Stabat tahun 2018Jenis penelitian: Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian observasional analitik dengan pendekatan studi cross sectional. Jumlah populasi sebanyak 32 orang, sampel yang digunakan dalam penelitian ini adalah total sampling sebanyak 32 orang.Hasil : Analisa data dengan menggunakan chi square test dengan derajat kepercayaan p 0,05. Berdasarkan hasil uji chi square hubungan pola makan dengan gastritis pada remaja di SMK Kesehatan Napsi’ah Stabat tahun 2018 dengan derajat kemaknaan (α) = 0,05 dan df = 1 diperoleh hasil perhitungan yaitu Sig (2-tailed) 0.001 (α) = 0,05, maka Ho ditolak dan Ha diterima.Kesimpulan : Kesimpulannya ada hubungan antara pola makan dengan gastritis pada remaja di SMK Kesehatan Napsi’ah Stabat tahun 2018. Disarankan hendaknya menjaga pola makan dengan baik khususnya pada frekuensi makan dengan makan teratur, makanan lengkap 3 kali sehari atau makanan selingan. Kata Kunci : Pola Makan, Gastritis